A peptide-modified solid lipid nanoparticle formulation of paclitaxel modulates immunity and outperforms dacarbazine in a murine melanoma model. (17th January 2019) - Banerjee, Indranil; De, Manjarika; Dey, Goutam; Bharti, Rashmi; Chattopadhyay, Sankha; Ali, Nahid; Chakrabarti, Partha; Reis, Rui L.; Kundu, Subhas C.; Mandal, Mahitosh
Abstract : Somatostatin receptor (SSTR) analog modified nanoparticles of paclitaxel (PSM) showed a superior anti-melanoma effect by inducing a favorable systemic immune response. Abstract : Melanoma is a highly aggressive skin cancer. A paclitaxel formulation of solid lipid nanoparticles modified with Tyr-3-octreotide (PSM) is employed to treat melanoma that highly expresses somatostatin receptors (SSTRs). PSM exerts more apoptotic and anti-invasive effects in B16F10 mice melanoma cells as compared to dacarbazine (DTIC), an approved chemotherapeutic drug for treating aggressive melanoma. Besides, PSM induces one of the biomarkers of immunogenic cell death in vitro and in vivo as confirmed by calreticulin exposure on the B16F10 cell surface. We observed a significant number of CD8 positive T cells in the tumor bed of the PSM treated group. As a result, PSM effectively reduces tumor volume in vivo as compared to DTIC. PSM also induces a favorable systemic immune response as determined in the spleen and sera of the treated animals. Importantly, PSM can reduce the number of nodule formations in the experimental lung metastasis model. Our experimentations indicate that the metronomic PSM exhibits remarkable anti-melanoma activities without any observable toxicity. This immune modulation behavior of PSM can be exploited for the therapy of melanoma and probably for other malignancies.